Online Identity and Cybercrime: Unmasking Threats in the Digital Age - Harahap, Rahma Hayati; Zikri, Muhammad Adfhol (CONTENT: Journal of Communication Studies, 2025)
Currently, the development of technology is increasingly massive, the development of technology has presently entered generation 5.0 and is heading towards 6.0. The development of technology at this time cannot be stopped due to the human will to develop continuously. Internet technology users in Indonesia reach more than 221 million people, and 139 million people use social media. This research aims to describe the negative impact of using internet technology in cyberspace, especially on social media, namely online crime or cybercrime involving personal online identity data that is misused. This research uses a qualitative approach that uses a literature study as its data collection. Which is sourced from existing journals, news, and blogs. And from this research we can see that crime in cyberspace itself has become increasingly massive, especially crimes that target a person's personal data or crimes by targeting a person's online identity such as catfishing, doxing, cyberbullying, and online-based fraud. This research can be an illustration that there are many crimes that occur in cyberspace and this research is expected to be a lesson for all parties to be more vigilant.